Targeting Adenosine Monophosphate‐Activated Protein Kinase by Metformin Adjusts Post‐Ischemic Hyperemia and Extracellular Neuronal Discharge in Transient Global Cerebral Ischemia. (October 2015) - Farbood, Yaghoob; Sarkaki, Alireza; Khalaj, Leila; Khodagholi, Fariba; Badavi, Mohammad; Ashabi, Ghorbangol
Abstract Objective I/R and its subsequent reactive hyperemia results in different adverse effects such as brain edema and BBB disruption. AMPK activation has been perceived as one of the target factors for I/R treatment. We investigated the effect of Met (an AMPK activator) on some physiological parameters including vascular responses, hyperemia, BBB disruption, and electrophysiological activity following tGCI. Methods Rats were pretreated with Met for two weeks and CC was administered half an hour before tGCI. Brain vascular responses, hyperemia, BBB disruption, and electrophysiological activity were evaluated following the ischemia. Results Met attenuated BBB disruption and reactive hyperemia in tGCI rats compared with the untreated I/R rats (p < 0.001). Met administration along with CC in the ischemic rats reversed the beneficial effects of Met on BBB disruption and reactive hyperemia (p < 0.001). Electrophysiological records indicated that Met increased spike rates in the ischemic rats comparing with I/R rats (p < 0.001), whereas, CC administration blocked the beneficial effects of Met on the neuronal discharges (p < 0.05). Conclusion We established a regulatory role for AMPK in vascular and electrophysiological responses to tGCI. Studies are ongoing to determine if activation of AMPK in the reperfusion period would offer similar protection.